2020
DOI: 10.1186/s12962-020-00219-7
|View full text |Cite
|
Sign up to set email alerts
|

Introduction of birth dose of hepatitis B virus vaccine to the immunization program in Ethiopia: an economic evaluation

Abstract: Background Hepatitis B virus (HBV) infection is an important cause of morbidity and mortality with a very high burden in Africa. The risk of developing chronic infection is marked if the infection is acquired perinatally, which is largely preventable through a birth dose of HBV vaccine. We examined the cost-effectiveness of a birth dose of HBV vaccine in a medical setting in Ethiopia. Methods We constructed a decision analytic model with a Markov process to estimate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Months since delivery should be prioritised as a prevention tool to reduce the risk of mother-to-child transmission. [22][23][24] Birth-dose vaccination was feasible in two high-volume maternity centres in urban Kinshasa, and was largely acceptable to mothers. Although we did not achieve vaccination within 24 h of birth for all infants, we showed that a high standard-of-care with adoption of a universal birth-dose vaccine is within reach in the Democratic Republic of the Congo.…”
Section: Discussionmentioning
confidence: 99%
“…Months since delivery should be prioritised as a prevention tool to reduce the risk of mother-to-child transmission. [22][23][24] Birth-dose vaccination was feasible in two high-volume maternity centres in urban Kinshasa, and was largely acceptable to mothers. Although we did not achieve vaccination within 24 h of birth for all infants, we showed that a high standard-of-care with adoption of a universal birth-dose vaccine is within reach in the Democratic Republic of the Congo.…”
Section: Discussionmentioning
confidence: 99%
“…Until such infrastructure is in place, HBV birth-dose should be prioritized as a prevention tool. [23][24][25] Birth-dose vaccination was feasible in two high-volume maternity centers in urban Kinshasa, DRC, and was largely acceptable to mothers. While we did not achieve vaccination within hours of birth for all infants, this feasibility study demonstrates that a higher standard-of-care is within reach in the DRC.…”
Section: Discussionmentioning
confidence: 99%
“…Some articles, focusing on vaccine supply chain per dose costs, report a range between US $0.43 and 1.21 (Mvundura et al, 2015). Others provide specific components estimations, such as cold chain (Constenla, 2015;Vaughan et al, 2020;Memirie et al, 2020), transportation (Cravioto et al, 2012), vehicles, gas price per liter and personnel costs (Vaughan et al, 2020;Portnoy et al, 2015). Some contributions interestingly distinguish between urban and rural facilities (Sch€ utte et al, 2015): delivery costs to rural centers, on average, are almost three times the costs of urban centers.…”
Section: Investments In Production Plant Andmentioning
confidence: 99%
“…Sensitization and social mobilization are often estimated together and range from US $0.05 for a child fully immunized against cholera to US $0.069(Mogasale et al, 2016). Program preparation costs include training as well: sometimes the cost of training is computed as a separate element(Memirie et al, 2020), while in other papers it is computed with other components,Gosset et al (2021) estimate the cost of planning, budgeting, training, for the introduction of the Hepatitis B birth dose, in Senegal as equal to US $0.00535 Preparation costs are sometimes included in operating costs and considered as direct costs together with cold chain maintenance and vaccine administration costs(Carias et al, 2015) or they are not distinguished from service delivery and monitoring and surveillance costs(Colombini et al, 2015) Vaccine administration costs Nineteen studies out of those selected contain information on materials and supplies costs, either in percentage or in monetary terms. As reported in Table4, costs per dose of vaccine supplies range from US $0.06(Sch€ utte et al, 2015) to US $0.19(Antill on et al, 2017).…”
mentioning
confidence: 99%